Quantum-Inspired Control Strategies for Reducing DC-Link Voltage Fluctuations in DFIG Wind Energy Converters - Sarika Shrivastava; Saifullah Khalid; Dinesh Kumar Nishad (IEEE Access)
The integration of renewable energy sources into power grids presents significant technical challenges, particularly regarding voltage stability and power quality. While Doubly-Fed Induction Generators (DFIGs) offer superior performance in variable wind conditions, their DC-link voltage fluctuations remain a critical concern affecting system reliability, component longevity, and grid compliance. This paper presents a quantum-inspired discrete Proportional-Integral (PI) controller to stabilize DC-link voltage in DFIG-based wind energy systems. The approach integrates quantum computing principles into classical control frameworks, creating a hybrid methodology that leverages quantum-inspired optimization while maintaining implementation feasibility on conventional hardware. By incorporating quantum-inspired algorithms into the Grid-Side Converter (GSC) control framework, the strategy dynamically adjusts PI gains using qubit-based probabilistic modeling—where control parameters exist simultaneously in multiple potential states, similar to quantum bits existing in both 0 and 1 states concurrently. This superposition-based optimization explores multiple solution spaces in parallel, achieving 40-50% faster convergence than classical methods. Simulations of a 1.5 MW DFIG system demonstrated a 69.6% reduction in steady-state voltage fluctuations (from 11.97% to 3.64%) and 73.8% improvement during symmetrical faults (from 33.33% to 11.31%), while limiting peak deviations to <10% during unsymmetrical faults (L-L-G/L-G). The controller maintained stable DC-link voltage at 1150V ±40V under normal operation and exhibited only 3.5% overshoot during fault conditions, significantly outperforming conventional PI and fuzzy controllers. This quantum-classical hybrid approach reduces mechanical stress on capacitors and converters, extends equipment lifespan, and enables higher renewable integration through improved grid stability while maintaining compliance with IEEE 1547–2018 standards.